THE ROLE OF TAX POLICY IN REDUCING POVERTY IN THE UNITED STATES - Azimov Allaberdi Urinovich (Ecominds Press, 2025)
This paper analyzes the role of U.S. tax policy in reducing poverty and documenting especially important tools, including the Earned Income Tax Credit (EITC) and the Child Tax Credit (CTC). The study presents a systematic literature review and some new data, and assesses the impact that these transitory policies have on alleviating poverty and suggests reforms to make them more effective. Results indicate that although current tax policies have played a role in reducing poverty they have also increased inequality, and specific policy measures need to be implemented. The study goes on to examine the history of tax policies targeting poverty reduction and compares the US tax system with the tax systems of other advanced industrial nations.
Keywords: Tax policy, poverty reduction, Earned income tax credit, Child tax credit, income inequality, social welfare, fiscal policy, United States